Impacts of EGR on RCCI engines management: A comprehensive review. (May 2022) - Elkelawy, Medhat; El Shenawy, E.A.; Mohamed, Sherif A.; Elarabi, Mostafa M.; Alm-Eldin Bastawissi, Hagar
Highlights: Benefits and drawbacks of EGR on RCCI engine management are discussed. EGR has a great impact on the RCCI engine's emission and performance characteristics. The higher EGR percentage has more benefits on lowering soot and NOx emissions. The collaborated regulation is important between EGR, premixed ratio, and DI timing. Abstract: Exhaust gas recirculation (EGR) has been one of the essential aspects to manage combustion phasing, in-cylinder reactivity, performance, and emissions in innovative RCCI engine operation. In this review, the effect of EGR on RCCI engine operations is reviewed and different techniques to employ EGR are discussed. Generally, RCCI engine operation needs EGR support, especially at high engine loads to limit the pressure increase rate, and around 50 percent of EGR may be essential based on fuel used and engine load. The RCCI combustion engine needs a substantially low EGR rate since the rate of burning is regulated by altering the mixture reactivity by employing two fuels having significantly varied reactivity. RCCI operation with cooled EGR yielded lower pressure rise rate, cyclic variation, and NOx emissions but greater THC emissions than hot EGR operation. Internal EGR and lower pressure of intake air achieved generally greater net indicated efficiencies and reduced emissions than that of the conventional RCCI combustion at low loads. At high load, the internal EGR mode is required to be turned off to minimize fuel efficiency loss. The higher EGR percentage has more benefits on extending maximum load and lowering soot and NOx emissions, whereas the combustion and indicated thermal combustion efficiencies decline to utilize higher EGR percentage. Thus, to accomplish the greater performance and efficient process of combustion, the collaborated regulation is important between EGR rate, premixed ratio, and direct-injection timing.